Determinants of caregiver burden of persons with disabilities in a rural district in Egypt - Eman Ramadan Ghazawy; Eman Sameh Mohammed; Eman Mohamed Mahfouz; Marwa Gamal Abdelrehim (BMC, 2020)
Abstract Background Family caregivers are critical partners in the plan of care of people with disabilities. The study aims to demonstrate the factor structure and internal consistency of the Caregiver Burden Inventory (CBI) among the studied caregivers of disabled persons and to determine the effects of patients' and caregivers' characteristics on the burden and its dimensions. Methods A cross-sectional study among 260 family caregivers of disabled patients was carried out in a randomly chosen rural area, Minia, Egypt, 2019. Exploratory factor analysis (EFA) was conducted to determine the factorial validity of the CBI. Multiple linear regression was used to identify the significant factors affecting the burden. Results Factor analysis resulted in a five-factor solution using 20 items (four for each dimension) accounting for 72.7% of the total variance. The CBI and its dimensions showed high internal consistency (Cronbach's alpha value > 0.70). Education of caregiver, family income, mental impairments, and mixed disabilities were significant predictors of total CBI burden. Conclusions CBI is an effective multidimensional measure of the caregiver burden of disabled subjects. Caregivers experienced a distinct level of burden that is determined by caregiver and care recipient characteristics. Therefore, support and individualized counseling services should be optimized.